Long-Distance Phasing of a Tentative “Enhancer” Single-Nucleotide Polymorphism With CYP2D6 Star Allele Definitions - Boone, Erin C.; Wang, Wendy Y.; Gaedigk, Roger; Cherner, Mariana; Bérard, Anick; Leeder, J. Steven; Miller, Neil A.; Gaedigk, Andrea (Frontiers in Pharmacology, 2020)
Background: The CYP2D6 gene locus has been extensively studied over decades, yet a portion of variability in CYP2D6 activity cannot be explained by known sequence variations within the gene, copy number variation or structural rearrangements. It was proposed that rs5758550 located 116 kb downstream of the CYP2D6 gene locus increases gene expression and thus contributes to variability in CYP2D6 activity. This finding has, however, not been validated. The purpose of the study was to address a major technological barrier, i.e. experimentally linking rs5758550, also referred to as the ‘enhancer’ SNP, to CYP2D6 haplotypes >100 kb away. To overcome this challenge is essential to ultimately determine the contribution of the ‘enhancer’ SNP to interindividual variability in CYP2D6 activity. Methods: A large ethnically mixed population sample (n=3162) was computationally phased to determine linkage between the ‘enhancer’ SNP and CYP2D6 haplotypes (or star alleles). To experimentally validate predicted linkages, DropPhase2D6, a digital droplet PCR (ddPCR)-based method was developed. 10X Genomics Linked-Reads were utilized as a proof of concept. Results: Phasing predicted that the ‘enhancer’ SNP can occur on numerous CYP2D6 haplotypes including CYP2D6 *1, *2, *5 and *41 and suggested that linkage is incomplete, i.e. a portion of these alleles do not have the ‘enhancer’ SNP. Phasing also revealed differences amongst the European and African ancestry data sets regarding the proportion of alleles with and without the ‘enhancer’ SNP. DropPhase2D6 was utilized to confirm or refute the predicted ‘enhancer’ SNP location for individual samples, e.g. of n=3 samples genotyped as *1/*41, rs5758550 was on the *41 allele of two samples and on *1 allele of one sample. Our findings highlights that the location of the ‘enhancer’ SNP must not be assigned by ‘default’. Furthermore, linkage between the ‘enhancer’ SNP and CYP2D6 star allele haplotypes was confirmed with 10X Genomics technology. We were unable, however, to verify selected haplotypes predicted by Ray et al (PMID 30520769). Conclusions: Since the ‘enhancer’ SNP can be present on a portion of normal, decreased, or no function alleles, the phase of the ‘enhancer’ SNP must be considered when investigating the impact of the ‘enhancer’ SNP on CYP2D6 activity.